Molecular cloning of a gene encoding the histamine H2 receptor. - Gantz, I (1991)
The H2 subclass of histamine receptors mediates gastric acid secretion, and antagonists for this receptor have proven to be effective therapy for acid peptic disorders of the gastrointestinal tract. The physiological action of histamine has been shown to be mediated via a guanine nucleotide-binding protein linked to adenylate cyclase activation and cellular cAMP generation. We capitalized on the technique of polymerase chain reaction, using degenerate oligonucleotide primers based on the known homology between cellular receptors linked to guanine nucleotide-binding proteins to obtain a partial-length clone from canine gastric parietal cell cDNA. This clone was used to obtain a full-length receptor gene from a canine genomic library. Histamine increased in a dose-dependent manner cellular cAMP content in L cells permanently transfected with this gene, and preincubation of the cells with the H2-selective antagonist cimetidine shifted the dose-response curve to the right. Cimetidine inhibited the binding of the radiolabeled H2 receptor-selective ligand [methyl-3H]tiotidine to the transfected cells in a dose-dependent fashion, but the H1-selective antagonist diphenhydramine did not. These data indicate that we have cloned a gene that encodes the H2 subclass of histamine receptors.